HIV viral exposure and mortality in a multicenter ambulatory HIV adult cohort, United States, 1995–2016. Issue 25 (25th June 2021) - Palella, Frank J.; Armon, Carl; Cole, Stephen R.; Hart, Rachel; Tedaldi, Ellen; Novak, Richard; Battalora, Linda; Purinton, Stacey; Li, Jun; Buchacz, Kate
Abstract : Abstract: The aim of this study was to identify viral exposure (VE) measures and their relationship to mortality risk among persons with HIV. Prospective multicenter observational study to compare VE formulae. Eligible participants initiated first combination antiretroviral therapy (cART) between March 1, 1995 and June 30, 2015. We included 1645 participants followed for ≥6 months after starting first cART, with cART prescribed ≥75% of time, who underwent ≥2 plasma viral load (VL) and ≥1 CD4+ T-lymphocyte cell (CD4) measurement during observation. We evaluated all-cause mortality from 6 months after cART initiation until June 30, 2016. VE was quantified using 2 time-updated variables: viremia copy-years and percent of person-years (%PY) spent >200 or 50 copies/mL. Cox models were fit to estimate associations between VE and mortality. Participants contributed 10, 453 person years [py], with median 14 VLs per patient. Median %PY >200 or >50 were 10% (interquartile range: 1%–47%) and 26% (interquartile range: 6%–72%), respectively. There were 115 deaths, for an overall mortality rate of 1.19 per 100 person years. In univariate models, each measure of VE was significantly associated with mortality risk, as were older age, public insurance, injection drug use HIV risk history, and lower pre-cART CD4. Based on model fit, most recent viral load and %PY >200 copies/mL provided the best combination of VE factors to predict mortality, although all VE combinations evaluated performed well. The combination of most recent VL and %PY >200 copies/mL best predicted mortality, although all evaluated VE measures performed well. Abstract : Supplemental Digital Content is available in the text